Impact of antithrombotic drugs on the accuracy of fecal occult blood testing for advanced colorectal neoplasia screening: a meta-analysis and systematic review - Pang, Shu-jie; Lin, Zhi-peng; Sun, Zhe; Zhang, Yu; Yuan, Zhen-gang; Yang, Ning (Zeitschrift für Gastroenterologie, 2022)
Background The current meta-analysis was conducted to determine whether antithrombotic drug use would affect the diagnostic accuracy of fecal occult blood testing for advanced colorectal neoplasia.Methods Articles published between 2000 and 2019 were systematically retrieved and screened according to the inclusion and exclusion criteria by two reviewers independently. Pooled analyses were conducted with a fixed-effect model if no apparent heterogeneity (I2 ≥ 50%) was found between studies; otherwise, the random effects model would be used. Sensitivity analysis and subgroup analysis were also conducted using Review Manager 5.3.Results Pooled analysis revealed that aspirin and nonsteroidal anti-inflammatory drugs were associated with a decrease in the positive predictive value of fecal occult blood testing for advanced colorectal neoplasia screening, with a RR of 0.89 (95% CI: 0.84–0.94) and 0.88 (95% CI: 0.84–0.93, p<0.001) respectively. Subgroup analysis based on data limited to high-quality studies, fecal immunochemical testing, or in Caucasians also showed that the use of aspirin/NSAID drugs decreased the accuracy for advanced colorectal neoplasia screening.Conclusion Aspirin/NSAIDs and direct oral anticoagulants rather than warfarin may decrease the diagnostic accuracy of fecal occult blood testing for advanced colorectal neoplasia screening.
Keywords: Fortgeschrittene kolorektale Neoplasie; Test auf okkultes Blut im Stuhl; Meta-Analyse; Antithrombotika